Pembangunan Pariwisata Baduy dan Dampaknya Terhadap Ekologi, Sosial, dan Budaya: Sebuah Studi Literatur - Satria Iman Prasetyo; Muhammad Naufal Rofi; Muhammad Basofi Firmansyah (Program Studi Ilmu Pemerintahan Universitas Muhammadiyah Buton, 2021)
Abstract: Tourism development must be sustainable. It is intended that tourism is not only used by current generations but future generations. The WTO (World Trade Organization) explains that sustainable tourism development must prioritize principles such as Ecological Sustainability, Social and Cultural Sustainability, and Economic Sustainability. The method used in this research is literature study. The data obtained were compiled, analyzed, and concluded in order to get conclusions about the topic under study. The results showed that tourism development in the Baduy traditional village was not yet in accordance with the principles of sustainable development. First, ecologically, the existence of tourism development actually has an impact on the threat of environmental destruction in the Baduy traditional village. This is known from the accumulation of plastic waste that is disposed of arbitrarily by tourists. Second, socially and culturally, the existence of tourism development has actually brought about changes in the values ​​of the Baduy community from traditional to modern. Third, economically, the existence of tourism development is able to improve the economy of the Baduy community by opening stalls in their yard. However, this economic increase is in line with environmental damage and changes in the socio-culture of the Baduy community. Keywords: tourism development, Baduy traditional village, ecology, economy, social and culture